2007
DOI: 10.1177/0193945907303083
|View full text |Cite
|
Sign up to set email alerts
|

Light Treatment for Neuropsychiatric Behaviors in Alzheimer's Disease

Abstract: Neuropsychiatric behaviors are common in people with Alzheimer's disease (AD) and make both professional and lay caregiving difficult. Light therapy has been somewhat successful in ameliorating disruptive behaviors. This randomized trial tested the effects of morning or afternoon bright light exposure compared with usual indoor light on the presence, frequency, severity, and occupational disruptiveness of neuropsychiatric behaviors in nursing home residents with AD. Light was administered for 1 hr daily (Monda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 32 publications
2
100
0
2
Order By: Relevance
“…Barrick et al [56] showed that ambient bright light is not effective in reducing agitation in institutionalized persons with dementia and may exacerbate this behavioral symptom in severely demented patients. Another study that described a light treatment in nursing home residents with AD showed small changes in neuropsychiatric behaviors (e.g., aggression, depression, eating disorders); however, the authors concluded that the magnitude of these changes do not represent clinically significant findings [57]. Onega et al [58] showed that bright light exposure was associated with significant improvement in depression and agitation, while participants receiving low-intensity light displayed no significant changes or higher levels of depression and agitation.…”
Section: Resultsmentioning
confidence: 99%
“…Barrick et al [56] showed that ambient bright light is not effective in reducing agitation in institutionalized persons with dementia and may exacerbate this behavioral symptom in severely demented patients. Another study that described a light treatment in nursing home residents with AD showed small changes in neuropsychiatric behaviors (e.g., aggression, depression, eating disorders); however, the authors concluded that the magnitude of these changes do not represent clinically significant findings [57]. Onega et al [58] showed that bright light exposure was associated with significant improvement in depression and agitation, while participants receiving low-intensity light displayed no significant changes or higher levels of depression and agitation.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-one RCTs met the inclusion criteria [40][41][42][43][44] and five main intervention categories emerged (Table 1): psychoeducational [13][14][15][16][17][18][19][20][21], physical activity [22][23][24][25], sensorial [26][27][28][29][30][31][32][33][34], staff-focused [35,36,37,38,40] and complex [41][42][43][44] (Table 2). Nineteen studies were two-arm RCTs [14,15,[17][18][19][21][22][23]25,26,[29][30][...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Nineteen studies were two-arm RCTs [14,15,[17][18][19][21][22][23]25,26,[29][30][31][32]35,38,40,41,43] and 12 were three-arm or more [13,16,20,24,27,28,33,34,36,37,42,44].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations